Gaming in Combinatorial Clock Auctions - Maarten Janssen; Vladimir Karamychev (Tinbergen Institute, 2013)
In recent years, Combinatorial Clock Auctions (CCAs) have been used around the world to allocate frequency spectrum for mobile telecom licenses. CCAs are claimed to significantly reduce the scope for gaming or strategic bidding. In this paper, we show, however, that CCAs significantly enhance the possibilities for strategic bidding. Real bidders in telecom markets are not only interested in the spectrum they win themselves and the price they pay for that, but also in the price competitors pay for that spectrum. Moreover, budget constraints play an important role. When these considerations are taken into account, CCAs provide bidders with significant gaming possibilities, resulting in high auction prices and problems associated with multiple equilibria and bankruptcy (given optimal bidding strategies).
urn:NBN:nl:ui:15-1765/38780
Keywords: D44; L96; 330; Combinatorial auctions; Telecom markets; Raising rivals' cost; Mobilkommunikation; Lizenz; Auktion; Auktionstheorie